2021
DOI: 10.1155/2021/8841720
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acupuncture on Neuroplasticity of Stroke Patients with Motor Dysfunction: A Meta-Analysis of fMRI Studies

Abstract: Importance. Acupuncture is an effective treatment for stroke, especially in the aspect of motor deficit. Many brain imaging studies of acupuncture have found significant changes in brain function after acupuncture treatment in order to reveal its underlying mechanisms in regulating neural plasticity. However, no definite consensus has been reached. Objective. To analyze the pattern of intrinsic brain activity variability that is altered by acupuncture compared with conventional treatment in stroke patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Motor dysfunction is one of the most common complications following stroke, which manifests as numbness and weakness of the limbs and even paralysis or spasms [ 13 , 52 ]. Motor dysfunction can seriously affect the quality of life and social participation of stroke patients.…”
Section: The Role Of Music Therapy In the Rehabilitation Poststrokementioning
confidence: 99%
“…Motor dysfunction is one of the most common complications following stroke, which manifests as numbness and weakness of the limbs and even paralysis or spasms [ 13 , 52 ]. Motor dysfunction can seriously affect the quality of life and social participation of stroke patients.…”
Section: The Role Of Music Therapy In the Rehabilitation Poststrokementioning
confidence: 99%
“…Although none of the studies had a clear study protocol, all expected outcome indicators were reported, including predetermined ones. We prefer to consider studies with two or more secondary outcome indicators reported to be at low risk for selectively reported data ( 24 ). Therefore, six studies had a low risk of bias in selective reporting, except Zhao's research ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…The NIH Consensus Conference ( 14 ) and publications ( 15 , 16 ) have demonstrated that acupuncture can improve the neurological motor deficit symptoms and become an acceptable alternative method for stroke rehabilitation. Recent research has shown that acupuncture was involved in regulating neural plasticity in patients with stroke, both functionally and structurally ( 17 , 18 ). Yanglingquan (GB34), the He-Sea point of the gall bladder meridian (Foot-Shaoyang), the confluence point of tendons, is one of the main points in post-stroke acupuncture approaches, such as Wang's twelve-needling at hands and feet method and Xingnao Kaiqiao needling method ( 19 ).…”
Section: Introductionmentioning
confidence: 99%